Comparative Study of The Dynamics of Riba Discourses Between Sharia Banks and Conventional Banks - Ganjar Eka Subakti; Muhammad Rindu Fajar Islamy (ITB AAS INDONESIA Surakarta, 2021)
This study aims to explore the comparison of views among banking practitioners in the dynamics of usury discourse. Lately, the trend of